Block and Gradient Copoly(2-oxazoline) Micelles: Strikingly Different on the Inside - Filippov, Sergey K; Verbraeken, Bart; Konarev, Petr V; Svergun, Dmitri I; Angelov, Borislav; Vishnevetskaya, Natalya S; Papadakis, Christine M; Rogers, Sarah; Radulescu, Aurel; Courtin, Tim; Martins, José C; Starovoytova, Larisa; et al. (The journal of physical chemistry letters, 2017)
Herein, we provide a direct proof for differences in the micellar structure of amphiphilic diblock and gradient copolymers, thereby unambiguously demonstrating the influence of monomer distribution along the polymer chains on the micellization behavior. The internal structure of amphiphilic block and gradient co poly(2-oxazolines) based on the hydrophilic poly(2-methyl-2-oxazoline) (PMeOx) and the hydrophobic poly(2-phenyl-2-oxazoline) (PPhOx) was studied in water and water-ethanol mixtures by small-angle X-ray scattering (SAXS), small-angle neutron scattering (SANS), static and dynamic light scattering (SLS/DLS), and 1H NMR spectroscopy. Contrast matching SANS experiments revealed that block copolymers form micelles with a uniform density profile of the core. In contrast to popular assumption, the outer part of the core of the gradient copolymer micelles has a distinctly higher density than the middle of the core. We attribute the latter finding to back-folding of chains resulting from hydrophilic-hydrophobic interactions, leading to a new type of micelles that we refer to as micelles with a "bitterball-core" structure.